Microcell and macrocell corrosion of steel bars and corrosion-induced concrete cracking in reinforced concrete slabs - Bui, Huy Tang (Nanyang Technological University, 2023)
Corrosion of steel bars and consequent corrosion-induced concrete cracking are multi-physics studies and they are mutually interactive with one another. Corrosion is regarded as one of the major factors causing premature failure of reinforced concrete (RC) structures. It not only induces cracking and spalling of concrete cover, but also reduces the steel bar’s cross-section and bond strength between the bar and the surrounding concrete. Microcell and macrocell current densities are the primary parameters governing structural deterioration rate. Their magnitude depends on various factors such as corrosion cause, environmental condition, steel bar geometry, concrete property, etc. After more than five decades in service, many RC structures have significantly degraded and structural engineers are now facing overhaul issues. Thus, it is of interest to thoroughly study microcell and macrocell corrosion kinetics of steel bars under different conditions, as well as consequent corrosion-induced cracks, to support structural engineers in their decision-making of maintenance and repair programmes. In this research, microcell and macrocell corrosion kinetics of corroded steel bars in RC slabs subjected to three corrosive environments (i.e., chloride contamination, carbonation, and combined chloride contamination cum carbonation), three uncorroded/corroded steel bar configurations (i.e., two cathode/anode ratios and contact conditions of steel bars) and repeated wetting-drying cycles were experimentally investigated. Electrochemical mechanisms based on thermodynamics, cathodic and anodic polarisation kinetics were proposed to interpret the test results. Besides, numerical models were developed to quantitatively predict variations of both microcell and macrocell current densities under different wetting and drying environments. As a consequence of steel bar corrosion, rust progressively accumulates on the steel bar’s surface, causing expansive pressure and cracking in surrounding concrete. To simulate uniform corrosion-induced concrete cracking, an enhanced analytical model was proposed, incorporating combined effects of time varying deformations of four layers (i.e., corroded steel bar; rust; cracked and uncracked concrete layers) and mechanical properties of rust. In addition, a mathematical model based on Asymmetrical Generalised von Mises function (AGvM model) was established to describe multi-peak asymmetrical nonuniform rust distribution around the steel bar’s circumference. Based on the rust layer obtained from the AGvM model, a 3D finite element (FE) model was developed to simulate nonuniform corrosion-induced cracks in concrete. The FE model showed its robustness by incorporating rust elements between the concrete and the steel bar. Besides, different temperature gradients were imposed on different rust elements to describe nonuniform rust expansion. Thus, it could realistically simulate the expansive nature of corrosion products and incorporate the confinement effect of the steel bar and the concrete. Experiments of six RC slabs with three different steel bar configurations and two corrosion levels were carried out to validate the AGvM and the FE models. The test results and FE models were then used to investigate the effects of different steel bar configurations on crack evolution in RC slabs. Finally, a 3D time-dependent nonuniform numerical model was introduced to simulate the entire corrosion process incorporating corrosion-induced concrete cracking. The model consisted of three consecutive stages including diffusion of aggressive substances in porous concrete, microcell and macrocell kinetics of corroded steel bars and corrosion-induced cracks. It showed that when cracks had been incorporated into the model, not only did the corroded area evolve faster, microcell and macrocell current densities significantly increased and distribution shape of the rust layer was more rounded.